PERAN KEPEMIMPINAN SUPERVISOR PADA EVENT WEDDING 1000/PAX DI BANQUET SECTION HOTEL ROYAL ASNOF PEKANBARU - Alisa Rahma Wahyuni; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Royal Asnof Hotel is a 3-star Hotel in Pekanbaru, this Royal Asnof Hotel provides facilities and services to arrange weddings held at the Royal Asnof Ballroom. The department that requested the holding of this wedding was the Banquet Part was part of the Food and Beverage Service Department at the Royal Asnof Hotel in Pekanbaru. Holding a wedding with 1000 invited guests / people is not efficient to be carried out for several reasons. Supervisors as manager leaders who play an important role in leading the wedding event 1000 / person. The purpose of this study was to analyze the planned implementation of the leadership role that was carried out by supervisors in the implementation of 1000 wedding events / people in the banquet section of the Royal Asnof Hotel Pekanbaru.Keywords: Banquet Supervisor, Banquet Section, Hotel.